Myth and measurement : the new economics of the minimum wage - Card, David E. (David Edward), 1956-; Krueger, Alan B. (Princeton University Press, 2016)
"In Myth and Measurement, David Card and Alan Krueger presented a powerful challenge to the conventional view that higher minimum wages necessarily reduce jobs for low-wage workers. In a work that has profoundly influenced public policy as well as the direction of economic research, the authors put standard economic theory to the test, using empirical methods and conducting a critical reexamination of existing literature on the minimum wage. Documenting the effects of the minimum wage on family earnings, poverty outcomes, and the stock market valuation of low-wage employers, they presented a wealth of evidence showing that increases in the minimum wage lead to increases in pay, but no loss in jobs. With a new preface discussing new data, Myth and Measurement continues to shift the terms of the debate on the minimum wage"--Back cover